In vitro release studies of methylmethacrylate liberation from acrylic cement powder - Bettencourt, A (2015)
Bone cement or polymethylmethacrylate (PMMA) is commonly used for anchoring cemented prosthesis to the bone. Cytotoxic effect of culture media exposed to PMMA powder may be related with long term problems associated with acrylic cement application, being the monomer (methylmethacrylate) one of the cement's component partly responsible for the cytotoxic effect. The present work reports the studies of monomer release from acrylic bone cement powder under different experimental conditions: setting time of PMMA (in solution and air) and different culture media composition. High-performance liquid chromatography was used for the determination of residual monomer. Mathematical models were applied to experimental dissolution data revealing that monomer release is lightly affected by the studied variables. The monomer release seems to be a surface phenomena, suggesting that the possible actions of monomer will mainly be due to the initial loss of non polymerized monomer rather than to further depolymerization of the already polymerized cement. (C) 2000 Elsevier Science B.V. All rights reserved.